PROSPECTS OF CASPIAN GAS AND ITS POTENTIAL MARKETS - ZIYADOV, Taleh (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Caspian region’s natural resources have been a controversial and hotly debated topic for a long time. Some have considered the region as an alternative to the Middle East, while others have preferred to simply ignore it altogether. In-deed, the region’s proven oil reserves are far smaller than that of the Middle East. Nevertheless, the im-portance of the Caspian Basin as another source of oil and gas supply and its strategic location come into play in keeping the region indispensable for the West. Since the Caspian states have opened their doors to foreign investors, most of the latter’s capital has gone to regions’ oil sector, while its gas sector has largely remained untouched. Caspian natural gas, which has not been seriously looked into until now, has far greater advantages in comparison with its oil. The U.S. Energy Information Administration (EIA) estimates the region’s proven gas reserves in Azerbaijan, Kazakhstan, Uzbekistan and Turkmenistan as much as 232 trillion cubic feet (tcf), compared to those in Saudi Arabia, which is the world’s number four in proven natural gas reserves. Today, these four states pro-duce roughly 4.5 tcf, and expect to reach a level of 8.7 tcf by 2010, which will be roughly 8% of the world’s projected total consumption of natural gas in 2010. According to a recent annual report of the International Energy Agency (IEA), in the next two decades, consumption of natural gas will continue to expand, especially in the area of energy generation. Most of the increase in energy demand will come from developing countries of Asia such as China and India. The geographical proximity of the Caspian Basin to the developing nations of Asia will be crucial in defining their energy policies toward the region. China, India and Japan are currently examining several alternative projects for procuring energy from the Middle East and the Caspian region to their domestic markets. Both Chinese and Japanese energy firms have been very active in acquiring interests in exploration and production of the Caspian oil and gas.